2017
DOI: 10.1111/cdev.12781
|View full text |Cite
|
Sign up to set email alerts
|

The Early Construction of Spatial Attention: Culture, Space, and Gesture in Parent–Child Interactions

Abstract: American and Israeli toddler-caregiver dyads (mean age of toddler = 26 months) were presented with naturalistic tasks in which they must watch a short video (N = 97) or concoct a visual story together (N = 66). English-speaking American caregivers were more likely to use left-to-right spatial structuring than right-to-left, especially for well-ordered letters and numbers. Hebrew-speaking Israeli parents were more likely than Americans to use right-to-left spatial structuring, especially for letters. When const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 72 publications
0
20
0
Order By: Relevance
“…This result replicates and extends previous evidence that spatial information affects infants' ability to extract ordered information in increasing/decreasing triplets of numerical arrays: infants' discriminated inversion in ordinal direction after habituation to left-to-right oriented numerical sequences but failed to do so when the sequences were right-to-left oriented (de Hevia et al, 2014). Overall, these findings show that a right-to-left orientation of visual sequences hinders infants' serial order abilities, possibly as a result of infants' exposure to early cultural practices that match the direction of the reading/writing system of their parents, which, in Western countries, is left-to-right oriented (see de Hevia et al, 2012 and de Hevia et al, 2014 for further discussion; see Göbel et al, 2018;McCrink et al, 2018 for evidence on the role of culture in shaping early spatial biases).…”
Section: Introductionmentioning
confidence: 92%
“…This result replicates and extends previous evidence that spatial information affects infants' ability to extract ordered information in increasing/decreasing triplets of numerical arrays: infants' discriminated inversion in ordinal direction after habituation to left-to-right oriented numerical sequences but failed to do so when the sequences were right-to-left oriented (de Hevia et al, 2014). Overall, these findings show that a right-to-left orientation of visual sequences hinders infants' serial order abilities, possibly as a result of infants' exposure to early cultural practices that match the direction of the reading/writing system of their parents, which, in Western countries, is left-to-right oriented (see de Hevia et al, 2012 and de Hevia et al, 2014 for further discussion; see Göbel et al, 2018;McCrink et al, 2018 for evidence on the role of culture in shaping early spatial biases).…”
Section: Introductionmentioning
confidence: 92%
“…The idea of nonslotted schemas to explain the SNARC effect is not far from Dehaene's LTM account of SNARC (MNL), the main difference being that our account stresses expertise. SNARC-like effects start to be detected in four-year-old children (McCrink, Shaki, & Berkowitz, 2014;Opfer, Thompson, & Furlong, 2010), therefore it seems that the kind of expertisefor this spatialization to appear-occurs by means of observational learning (for a review see McCrink & Opfer, 2014;Patro, Nuerk, Cress, & Haman, 2014) through the interaction between infants and caregivers (McCrink, Caldera, & Shaki, 2018) via storybook reading for example. In cultures in which numbers (left to right in Israel) and words (right to left in Israel) are written in opposite directions, nonslotted schemas seem less or not at all spatialized (Shaki et al, 2009), which suggests that for SNARC-like effects to be observed, the spatial biases in a culture must not be opposite to each other.…”
Section: Accounting For Both Snarc and Spoarc Effects: An Expertise Amentioning
confidence: 99%
“…For example, de Hevia et al 2012 four-year-old children already exhibit culture-specific spatial biases (McCrink, Shaki, & Berkowitz, 2014;Opfer, Thomson, & Furlong, 2010). This spatial influence is thought to occur mainly by means of observational learning (for a review, see McCrink & Opfer, 2014;Patro et al, 2016), for instance through the interaction between infants and caregivers (McCrink, Caldera, & Shaki, 2017).…”
Section: Introductionmentioning
confidence: 99%